Construction Stakeholders’ Perceptions of Occupational Safety and Health Risks in Malaysia - Abas, Nor Haslinda; Ahmad Jalani, Amirull Firdaus; Mohd Affandi, Haryanti (International Journal of Sustainable Construction Engineering and Technology, 2022)
Malaysia’s construction industry is known as a hazardous industry, which has been overwhelmed with accidents for a long time. It is perceived that the control of accidents requires the participation of various stakeholders at every stage of the construction process. However, the primary responsibility for site safety has traditionally and commonly been ascribed to general/principal contractors. In practice, it is believed that different stakeholders tend to perceive OSH risks differently due to the diversity of their project interests. This study attempted to understand the similarities and differences of OSH risk perceptions among different construction stakeholder groups. In this study, a survey, which consisted of four different cases, was developed to represent the hazards or risks that can occur in selected activities during the construction process. Each case consists of two different scenarios, in which each scenario presents a combination of different issues that posed different hazards or risks. Survey was distributed to different project stakeholder groups currently working at construction sites, including designers, site management/technical teams, safety personnel, and other relevant individuals, with the purpose of exploring their OSH risk perceptions. The participants were required to determine the magnitude of the risk that each scenario presented, based on 1 (low) to 10 (extremely high) scale. The Intraclass Corellation Coefficient (ICC) and Kruskal-Wallis tests were carried out to test the similarities and differences within and between groups of participants. Findings of the present study revealed a high degree of similarity of OSH risk perception within and among stakeholder groups. The current research made a contribution by providing evidence on the similarities and differences among construction stakeholders’ perceptions in Malaysia, particularly those who are site-based.